Evaluation of GPS Data Processing for Platform Network Simulation using Commercial Software - Widjajanti, Nurrohmat (2008)
Measurement of remote location using GPS is categorized as a long baseline data due to long distance of GPS receiver to the reference station. Processing of long baseline data requires special processing technique to eliminate certain errors and resolve any processing ambiguity. This processing technique may not be within the capability of most commercial software available in the market. Hence this paper presents the processing of long baseline GPS data (synonym with GPS offshore platform data) using four renowned commercial GPS processing softwares in order to assess their capability to perform the above task. This work is based in simulated deformation of an offshore platform at Universiti Teknologi Petronas (UTP) with reference to far away IGS data. The result revealed that the commercial softwares are capable of processing short baselines up to around 36 km only with accuracy not more than 10 mm. Since offshore platform is typically around 150 km offshore it is obvious that their GPS data processing for the purpose of deformation and subsidence monitoring could not be done using commercial softwares.